Medical resource utilization and costs among Australian patients with genotype 1 chronic hepatitis C: results of a retrospective observational study. (2nd January 2017) - McElroy, Heather J.; Roberts, Stuart K.; Thompson, Alex J.; Angus, Peter W.; McKenna, Sarah Jane; Warren, Emma; Musgrave, Sharon
Abstract: Objective: To evaluate medical resource utilization (MRU) and associated costs among Australian patients with genotype 1 chronic hepatitis C (GT1 CHC), including both untreated patients and those receiving treatment with first-generation protease inhibitor-based regimens (telaprevir, boceprevir with pegylated interferon and ribavirin). Methods: Medical records were reviewed for a stratified random sample of GT1 CHC patients first attending two liver clinics between 2011–2013 (principal population; PP), supplemented by all GT1 CHC patients attending one transplant clinic in the same period (transplant population; TP). CHC-related MRU and associated costs are reported for the PP by treatment status (treated/not treated) stratified by baseline fibrosis grade; and for the TP for the pre-transplant, year of transplant and post-transplant periods. Results: A total 1636 patients were screened and 590 patients (36.1%) were included. Comprehensive MRU data were collected for 276 PP patients (F0–1 n  = 59, F2 n  = 58, F3 n  = 53, F4 n  = 106; mean follow-up = 17.3 months). Thirty-eight (13.8%) were treatment-experienced prior to enrolment; 55 (19.9%) received triple therapy during the study. Data were collected for 112 TP patients (mean follow-up = 29.9 months), 33 (29.5%) received a transplant during the study, and 51 (45.5%) beforehand. The annual direct medical costs, excluding drug costs, were higher among treated PP vs untreated PP (AU$: $1, 954 vs $1, 202); and year of transplant TP vs pre-/post-transplant TP (AU$: pre-transplant $32, 407, transplant $155, 138, post-transplant $7, 358). Limitations: To aid interpretation of results, note that only patients with GT1 CHC who are actively managed are included, and MRU data were collected specifically from liver outpatient clinics. That said, movement of patients between hospitals is rare, and any uncaptured MRU is expected to be minimal. Conclusions: CHC-related MRU increases substantially with disease severity. These real-world MRU data for GT1 CHC will be valuable in assessing the impact of new hepatitis C treatments.